Exchanges: Conversation with Jayne Malenfant, McGill University - Sanz, Penelope C. (Engaged Scholar Journal, 2019)
In the Exchanges, we present conversations with scholars and practitioners of community engagement, responses to previously published material, and other reflections on various aspects of community-engaged scholarship meant to provoke further dialogue and discussion. In this section, we invite our readers to offer their thoughts and ideas on the meanings and understandings of engaged scholarship, as practiced in local or faraway communities, diverse cultural settings, and in various disciplinary contexts. We especially welcome community-based scholars’ views and opinions on their collaborations with university-based partners in particular and engaged scholarship in general. In this issue, we profile the perspectives of young scholars. Here we feature a conversation between Penelope Sanz, who recently obtained her Ph.D. in Interdisciplinary Studies from the University of Saskatchewan and who serves as the Journal’s pioneering managing assistant, and Jayne Malenfant, a 2018 Pierre Elliott Trudeau Scholar, Vanier Scholar, and Ph.D. Candidate at McGill University in the Department of Integrated Studies in Education. A young engaged scholar working with the homeless in Montreal, Jayne talks about her on-going study on how homelessness impacts young people’s education. She looks at the challenges of accessing educational institutional support, an issue, she says, close to her heart as she was once a homeless youth herself. She reflects on the need for academia to open more spaces for young researchers undertaking engaged scholarship to involve the homeless youths themselves in the search for solutions.